Improved orthogonal flux corrector-based rotor flux estimation in PMSM sensorless control - Cheng, Siyuan (2024)
In a permanent magnet synchronous machine (PMSM) system, the voltage mode-based rotor flux observer suffers from DC drift, primarily due to measurement errors, parameter variations, and non-zero initial states. To address this issue, the second-order flux observer (SOFO) is utilized, equipped with filtering capability aimed at reducing harmonic components. However, the DC offset induced by external disturbances cannot be completely eliminated by the second-order transfer function alone. Traditional magnetic flux correctors typically update correction values only at zero-crossing points of the magnetic flux. In this study, we propose an improved orthogonal flux corrector (IOFC) that combines a generalized integrator to effectively filter out the DC offset. In comparison with traditional OFC methods, our approach involves reconstructing two magnetic linkage functions, thereby doubling the correction frequency within a single cycle. Consequently, the frequency of correction term updates is threefold compared to conventional OFC methods. Finally, IOFC is implemented and tested on a PMSM platform for experimental verification.